2016
DOI: 10.3892/mmr.2016.5164
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine attenuates osteoarthritis of the knee via modulation of inflammatory responses in a rabbit model

Abstract: The aim of the present study was to investigate the efficacy of ketamine in attenuating osteoarthritis (OA) and modulating the expression of inflammatory mediators. A rabbit OA model was established by knee immobilization using plaster bandages. After six weeks, rabbits were randomly allocated into four groups (n=6/group): Normal saline, Ket60, Ket100, and Ket200 and twice a week for four weeks the rabbits received an intra-articular injection of saline, or 60, 100 or 200 µmol/l ketamine, respectively. One wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
5
0
2
Order By: Relevance
“…# P < 0.05, ## P < 0.01, significantly different as compared to control group; *P < 0.05, **P < 0.01, significantly different as compared to the AA group and IL-6 in AA rats. These results are found in accordance with earlier report where KET showed to reduce the level of TNF-α [13]. The transcription factor NF-κB has been well documented as a critical controller of inflammation in RA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…# P < 0.05, ## P < 0.01, significantly different as compared to control group; *P < 0.05, **P < 0.01, significantly different as compared to the AA group and IL-6 in AA rats. These results are found in accordance with earlier report where KET showed to reduce the level of TNF-α [13]. The transcription factor NF-κB has been well documented as a critical controller of inflammation in RA.…”
Section: Discussionsupporting
confidence: 93%
“…In recent report by Hanna et al [12], ketamine showed reduction in pain in rheumatoid arthritis patient with comorbid fibromyalgia. Moreover, ketamine also showed reduction of the Mankin's score, decreased TNF-α and NF-κB p65 expression levels, and increased the level of IL-10 expression in a concentration-dependent manner in a rabbit model of OA [13]. However, the mechanism by which ketamine ameliorates the RA has been poorly understood [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine has anti-inflammatory effects, modulating the production of different proinflammatory mediators. A recent study using a rabbit model of gonarthrosis found that ketamine suppressed the inflammatory response in osteoarthritis, 28 whereas a systematic review concluded that intraoperative ketamine reduces the postoperative IL-6 inflammatory response in surgical patients. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus hat Ketamin entzündungshemmende Wirkungen, indem es die Produktion verschiedener proinflammatorischer Mediatoren moduliert. Eine kürzlich durchgeführte Studie in einem Kaninchenmodell für Gonarthrose ergab, dass Ketamin die Entzündungsreaktion bei Arthrose unterdrücken kann 36 , während eine systematische Überprüfung zu dem Schluss kam, dass intraoperatives Ketamin die postoperative IL-6-Entzündungsreaktion bei chirurgischen Patienten reduziert 37 .…”
Section: Systemisches Managementunclassified